PHYTOCONSTITUENTS, PIGMENTS , G.C.M.S. ANALYSIS AND ALLELOPATHY EFFECT OF ALTERNANTHERA FICOIDEA (L.) P. BEAUV - RESHMA B PATIL; BASAVARAJ A KORE (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim was to investigate phytoconstituents, composition of pigments, gas chromatography mass spectrometry (GCMS) and allelopathy of Alternanthera ficoidea (L.) P. Beauv. Methods: Qualitative phytochemical analysis was carried out by the method of Paech and Tracey using five different solvent systems (D.W., ether, chloroform, ethanol, and methanol). Methanol leaf extract of this plant was analyzed using GCMS. Chlorophylls, carotenoid, and polyphenols were estimated by following standard methods. Allelopathy effect was studied using leaf leachets on seeds of jowar and mung. Result and Conclusion: Investigation of above parameters in A. ficoidea showed presence of large amount of pharmaceutically important phytochemicals like tannins, saponins, phytols, carotenoids, xanthophylls and polyphenols. It indicates that this weed can be used in herbal medicines and dietary supplements. Since this weed is showing allelopathy effect it should be eradicated from fields before it spreads and occupies the place meant for crop plants. Keywords: Allelopathy, Alternanthera ficoidea, Exotic weed, Phytochemicals.